Methoden zur Erforschung grammatischer Strukturen in historischen Quellen Vom Einzelfall zum System - Braun, Christian; Scherr, Elisabeth (Lingua Historica Germanica, 2023)
In order to counteract introspective approaches and the detailed analysis of individual cases in historical grammar research, this volume brings together essays by experts working on the empirical analysis of (text)grammatical structures in Old German and Middle High German texts, also taking into account sociolinguistic parameters. These scholars have developed promising concepts and outline their projects here.